Phytohormones Trigger Drought Tolerance in Crop Plants: Outlook and Future Perspectives - Iqbal, Shehzad; Wang, Xiukang; Mubeen, Iqra; Kamran, Muhammad; Kanwal, Iqra; Díaz, Gonzalo A.; Abbas, Aqleem; Parveen, Aasma; Atiq, Muhammad Nauman; Alshaya, Huda; Zin El-Abedin, Tarek K.; Fahad, Shah (Frontiers in Plant Science, 2022)
In the past and present, human activities have been involved in triggering global warming, causing drought stresses that affect animals and plants. Plants are more defenseless against drought stress; and therefore, plant development and productive output are decreased. To decrease the effect of drought stress on plants, it is crucial to establish a plant feedback mechanism of re-sistance to drought. The drought reflex mechanisms include the physical stature physiology and biochemical, cellular, and molecular-based processes. Briefly, improving the root system, leaf structure, osmotic-balance, comparative water contents and stomatal adjustment are considered as most prominent features against drought resistance in crop plants. In addition, the signal transduc-tion pathway and reactive clearance of oxygen are crucial mechanisms for coping with drought stress via calcium and phytohormones such as abscisic acid, salicylic acid, jasmonic acid, auxin, gibberellin, ethylene, brassinosteroids and peptide molecules. Furthermore, microorganisms, such as fungal and bacterial organisms, play a vital role in increasing resistance against drought stress in plants. The number of characteristic loci, transgenic methods and the application of exogenous substances (nitric oxide, (C28H48O6) 24-epibrassinolide, proline, and glycine betaine) are also equally important for enhancing the drought resistance of plants. In a nutshell, the current review will mainly focus on the role of phytohormones and related mechanisms involved in drought tol-erance in various crop plants.